DIRECTIONS FOR TRANSFERRING FOREIGN EXPERIENCE OF SUSTAINABLE DEVELOPMENT OF THE AGRO-FOOD COMPLEX TO THE RUSSIAN ECONOMY - Elena DERUNOVA; Marianna VASILCHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Sustainable development of agriculture is a prerequisite for increasing food volumes and implementing technological transformations. The paper presents an assessment of various concepts and mechanisms for managing sustainability in agriculture in developed countries. The purpose of the work is to study foreign experience in managing sustainable agricultural development and to develop directions for transferring positive experience to the agricultural sector of the Russian economy. The important role of digital technologies in agriculture is confirmed and the need to stimulate their implementation in various sub-sectors is substantiated. The main options, models and technologies for achieving sustainable development of agriculture in advanced countries are studied. The need to apply a multi-level strategy for managing sustainable development of agriculture in Russia is substantiated. The foreign experience of sustainable development of the agro-food complex is generalized and systematized, the author's models are presented: European, American, Latin and Japanese. Based on these models, directions for transferring positive foreign experience of sustainable development of the agro-food complex to the Russian economy are proposed. The practical value of the results obtained lies in the possibility of their use in the development of programs, strategies and mechanisms for the sustainable development of the agro-food complex of the country and regions to increase food production and introduce advanced technologies.